SILDENAFIL PLUS UNDECANOATE AND SILDENAFIL ALONE IN THE TREATMENT OF TYPE 2 DIABETIC PATIENTS WITH ERECTILE DYSFUNCTION. (8th October 2012) - Zhang, Erhong; Zhang, Bin; Chen, Jun; Zang, Zhijun; Qi, Tao; Zhang, Bin
Abstract : Objectives: To compare the efficacy and safety of Sildenafil plus Undecanoate (Andriol) with those of Sildenafil alone in the treatment of Type 2 diabetic patients with erectile dysfunction (ED). Methods: Forty patients with Type 2 diabetic ED were randomly divided into two Groups, aged 32∼55 years. These patients in two groups were age-matched. Group A received 50 mg Sildenafil 30 min before planned sexual activity for 12 weeks, and Group B were given 40 mg Andriol after breakfast and supper daily and give 50 mg Sildenafil 30 min before sexual activity for 12 weeks. Before and after the treatment, IIEF-5 score, the intercourse satisfaction, and the drug- related side effects were evaluated. Results: Erectile function of both groups was obviously improved after treatment than that before treatment. IIEF-5 scores were (11.3±2.1), (16.2±2.4) respectively at baseline and post-treatment in Group A, and (10.8±1.9), (18.4±2.2) in Group B. The improvement is more significant in Group B. In addition, Group B subjects were more satisfied with treatment and had a higher intercourse success rate. As for the side effects, there was no significant difference in two groups. The majority of side events were mild, the most commonly reported treatment-related events were dizziness and tinnitus. Conclusions: Undecanoate combined with Sildenafil maybe more effective to improve the erectile function than Sildenafil alone in Type 2 diabetic patients with erectile dysfunction.